Phosphate starvation regulon of Salmonella typhimurium. - Foster, J W (1986)
Several phosphate-starvation-inducible (psi) genetic loci in Salmonella typhimurium were identified by fusing the lacZ gene to psi promoters by using the Mu d1 and Mu d1-8 bacteriophages. Although several different starvation conditions were examined, the psi loci responded solely to phosphate deprivation. A regulatory locus, psiR, was identified as controlling the psiC locus. The psiR locus did not affect the expression of the Escherichia coli phoA locus or any of the other psi loci described.